Um estudo de caso em recuperação de dados utilizando data carving aplicado à computação forense - PEREIRA, Eric Felipe de Oliveira (2019)
The area of Computer Forensics is steadily growing, especially in Brazil, so it is necessary studies that order recurring topics in the day to day of a forensic expert. Moreover, every day, we store several and several files in digital media, some of paramount importance, and for some reason such data may be intentionally or unintentionally damaged or lost. For that reason, the study in data recovery is required, primarily for NTFS file systems, the most used by end-users. This work presents a comparative assessment of data recovery tools, in order to aggregate knowledge in the studied area. To do this, a bibliographical survey was made on the main concepts relating to data retrieval, and subsequently a case study to analyze the recovery tools. Thus, at the end of the case study, it was verified that part of the tested tools had positive results, retrieving data on the NTFS file system.